2012
DOI: 10.1111/j.1365-3083.2012.02732.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally Circulating CD4+ FOXP3+ CXCR3+ T Regulatory Cells Correlate with Renal Allograft Function

Abstract: Background Peripheral immunoregulation depends on T regulatory cell trafficking into the allograft in order to modulate the local alloresponse. Little is known about the relevance of trafficking receptors for Tregs after solid organ transplantation in humans. In this study expression of the peripheral chemokine receptors CXCR3 and CCR5 on CD4+FOXP3+ Treg cells was analyzed and correlated with allograft function in renal transplant recipients. Methods Flow cytometry analysis of peripheral blood mononuclear ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…There might be other chemokines that also had the effect of recruiting Tregs into inflammatory tissue. Hoerning et al [ 30 ] found not only CXCR3 but also CCR5 was related to the trafficking function of Tregs in renal transplantation in mice. Although further investigation is needed, our results still support CXCR3 as an important chemokine for the migratory function of Tregs in renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…There might be other chemokines that also had the effect of recruiting Tregs into inflammatory tissue. Hoerning et al [ 30 ] found not only CXCR3 but also CCR5 was related to the trafficking function of Tregs in renal transplantation in mice. Although further investigation is needed, our results still support CXCR3 as an important chemokine for the migratory function of Tregs in renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the differentiation of Tregs as well as Th1 effector cells to express the corresponding chemokine receptor Cxcr3 is likely to play an important role in promoting their co-localization within renal allografts. CXCR3 þ peripherally circulating CD4 þ FOXP3 þ Tregs have been found in patients to correlate with renal allograft function, again suggesting a role for CXCR3 in their recruitment into peripheral sites of inflammation by their ligand CXCL10 (IP-10) (43,44). Whereas the chemokine receptor Ccr4 [C-C chemokine receptor type 4] has been found to be essential for the migration of Tregs into sites of inflammation in some models (45), Ccr4-deficient mice did not show any defect in Treg recruitment nor in the development of spontaneous tolerance in the DBA/2 to C657BL/6 mouse kidney transplant model (21), implying that usage of alternative chemokine receptors, including Cxcr3, may be more important in this setting.…”
Section: Donor-specific Tolerance In Kidney Transplantmentioning
confidence: 99%
“…10 For example, chemokine receptor CCR7, which is expressed on naïve-and effector/memory-like T-cell subsets, is critical for the circulation of Tregs in the lymph nodes. 13 The elevated expression of peripheral CXCR3 facilitates Treg migration to inflammatory sites to improve graft function, 14 whereas CCR4 supports Treg trafficking to airway mucosal tissues to attenuate allergic airway inflammation. 11 Another chemokine receptor, CCR6, is involved in the recruitment of pathogenic T cells to skin and mucosa-associated tissues in experimental autoimmune encephalitis.…”
Section: Introductionmentioning
confidence: 99%
“…12 Chemokine receptors CXCR3 and CCR4 are predominantly expressed on skin-infiltrating lymphocytes. 13 The elevated expression of peripheral CXCR3 facilitates Treg migration to inflammatory sites to improve graft function, 14 whereas CCR4 supports Treg trafficking to airway mucosal tissues to attenuate allergic airway inflammation. 15 The blocking of CCR4 expression has been shown to result in the selective depletion of effector-type FOXP3 + CD4 + Tregs and the enhancement of tumor immunity in adult T-cell leukemia-lymphoma.…”
mentioning
confidence: 99%